A comparative study of physical and chemical activation of rice straw derived biochar to enhance Zn+2 adsorption. (September 2021) - Sakhiya, Anil Kumar; Baghel, Paramjeet; Anand, Abhijeet; Vijay, Virendra Kumar; Kaushal, Priyanka
Abstract: Rice straw management is a significant challenge in northern India. In-situ combustion of rice straw is a practice to clear the agricultural field. Therefore, an attempt was made to add value to rice straw by producing activated biochar and check its efficacy to adsorbed Zn +2 contaminants from the water. The influence of pH, contact time, initial metal concentration, and temperature on the sorption rate had been analyzed in detail. The findings show that physical and chemical activated biochar has a microporous internal structure, with a specific surface area of 105.21 and 255.88 m 2 g −1 . The pseudo-second-order and Freundlich models accurately described the adsorption kinetics and isotherms individually. Zn +2 adsorption capacity of potassium acetate-activated biochar was greater than those of steam-activated biochar. Kinetics suggests spontaneous and endothermic reactions. Cost analysis indicates that rice straw-derived activated biochar was economical compared to other biomass, which shows high scale-up potential. Graphical abstract: Unlabelled Image Highlights: Activated-biochar derived from rice straw to remove Zn +2 from aquas CH3 COOK activated biochar had a higher surface area than H2 O activated biochar. R- CH3 COOK biochar had higher Zn +2 removal efficiency than R- H2 O biochar. Kinetic studies show multi-layer adsorption on biochar surfaces. Economic analysis suggests scale-up potential.